Black box, white cube, gray zone: Dance exhibitions and audience attention - Bishop, Claire (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
Relocated from the “black box” of experimental theatre to the “white cube” of the gallery, dance in the museum brings about new forms of performance —the dance exhibition— and new protocols of audience behavior that permit, even encourage, smartphone photography. This is the “gray zone” of recent performance, which is both a symptom of, and compensation for, the virtualization of contemporary perception.